UPAYA AUSTRALIA DALAM PENGURANGAN EMISI GAS KARBON MELALUI KERJASAMA IAFCP DI KABUPATEN KAPUAS, KALIMANTAN TENGAH - Sari, Kadek Rina Febriana (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT Deployment of carbon emissions became one of the problems for the environment that has to be dealt internationally. Australia and Indonesia are two countries which have strong commitment in international policy in reducing carbon emissions through Reducing Emission from Deforestation and Degradation+ (REDD+). That commitment has been reached in the form of bilateral cooperation with Indonesia Australia Forest Carbon Partnership (IAFCP). Through IAFCP, Australia has made several efforts with Indonesia government in reducing emissions from forest degradation and deforestation. This study discuss about the efforts of Australia in terms of reducing carbon emissions through the cooperation with IAFCP that are located in Kapuas Region, Central Kalimantan. This study will be analyzed by using the Green theory and concepts of bilateral cooperation, within the time frame tempos from 2008 the begin of the cooperation until 2014 expiry year of the cooperation. Keywords : Australia, Carbon emmision, REDD+, IAFCP, Indonesia